A Security Analysis on OpenSIPS - Satrya, Gandeva Bayu; Nicovandia, Muhammad Caesara (IJAIT (International Journal of Applied Information Technology), 2019)
IP Telephony, Internet Telephony, Digital Phone or often also called VoIP (Voice Over Internet Protocol) is a technology that allows long-distance voice conversations with the Internet. The increasing number of VoIP users and other IP-based multimedia streaming services naturally raises security issues. Many users are likely to lose their privacy in communication. To overcome this security problem a security system must be implemented. Implementing a security system will use VPN Gateway using SSL and TLS encryption on the VoIP server. The VPN Gateway method is used to build a private network so that only certain users can use the private network. The TLS method is used to secure a user signaling session to the server. From the test results obtained that the VoIP server that uses VPN Gateway and TLS on the server can overcome the attacks e.g., eavesdropping, attacking authentication, teardown session, and denial of service.